Racial and Ethnic Differences in the Prevalence of Do-Not-Resuscitate Orders among Older Adults with Severe Traumatic Brain Injury. (December 2022) - Hatfield, Jordan; Fah, Megan; Girden, Alex; Mills, Brianna; Ohnuma, Tetsu; Haines, Krista; Cobert, Julien; Komisarow, Jordan; Williamson, Theresa; Bartz, Raquel; Vavilala, Monica; Raghunathan, Karthik; et al.
Background: Older adults suffering from traumatic brain injury (TBI) are subject to higher injury burden and mortality. Do Not Resuscitate (DNR) orders are used to provide care aligned with patient wishes, but they may not be equitably distributed across racial/ethnic groups. We examined racial/ethnic differences in the prevalence of DNR orders at hospital admission in older patients with severe TBI. Methods: We conducted a retrospective cohort study using the National Trauma Databank (NTDB) between 2007 to 2016. We examined patients ≥ 65 years with severe TBI. For our primary aim, the exposure was race/ethnicity and outcome was the presence of a documented DNR at hospital admission. We conducted an exploratory analysis of hospital outcomes including hospital mortality, discharge to hospice, and healthcare utilization (intracranial pressure monitor placement, hospital LOS, and duration of mechanical ventilation). Results: Compared to White patients, Black patients (OR 0.48, 95% CI 0.35-0.64), Hispanic patients (OR 0.54, 95% CI 0.40-0.70), and Asian patients (OR 0.63, 95% CI 0.44-0.90) had decreased odds of having a DNR order at hospital admission. Patients with DNRs had increased odds of hospital mortality (OR 2.16, 95% CI 1.94-2.42), discharge to hospice (OR 2.08, 95% CI 1.75-2.46), shorter hospital LOS (−2.07 days, 95% CI −3.07 to −1.08) and duration of mechanical ventilation (−1.09 days, 95% CI −1.52 to −0.67). There was no significant difference in the utilization of ICP monitoring (OR 0.94, 95% CI 0.78-1.12). Conclusions: We found significant racial and ethnic differences in the utilization of DNR orders among older patients with severe TBI. Additionally. DNR orders at hospital admission were associated with increased in-hospital mortality, increased hospice utilization, and decreased healthcare utilization. Future studies should examine mechanisms underlying race-based differences in DNR utilization.